2017
DOI: 10.1016/j.intimp.2017.08.028
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-omega: Current status in clinical applications

Abstract: Since 1985, interferon (IFN)-ω, a type I IFN, has been identified in many animals, but not canines and mice. It has been demonstrated to have antiviral, anti-proliferation, and antitumor activities that are similar to those of IFN-α. To date, IFN-ω has been explored as a treatment option for some diseases or viral infections in humans and other animals. Studies have revealed that human IFN-ω displays antitumor activities in some models of human cancer cells and that it can be used to diagnose some diseases. Wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 102 publications
1
44
1
Order By: Relevance
“…Second, some studies showed that IFN-ε exhibits antiviral activity against cells derived from species that have near relatives and are expected to be homologous cells [23, 25]. Third, IFN-ε differs from IFN-α in macrophages by inducing an antiviral state mediated by more different factors [4]. Studies have revealed that numbers of genes or expression levels induced by type I IFN, IL-6, and TNF pathways in response to IFN-α and IFN-ε are not identical, in spite of some overlap among IL-1α, IL-1RA, IL-4, VEFG, and GCSF [4].…”
Section: Biological Activities Of Type I Ifnsmentioning
confidence: 99%
See 4 more Smart Citations
“…Second, some studies showed that IFN-ε exhibits antiviral activity against cells derived from species that have near relatives and are expected to be homologous cells [23, 25]. Third, IFN-ε differs from IFN-α in macrophages by inducing an antiviral state mediated by more different factors [4]. Studies have revealed that numbers of genes or expression levels induced by type I IFN, IL-6, and TNF pathways in response to IFN-α and IFN-ε are not identical, in spite of some overlap among IL-1α, IL-1RA, IL-4, VEFG, and GCSF [4].…”
Section: Biological Activities Of Type I Ifnsmentioning
confidence: 99%
“…Third, IFN-ε differs from IFN-α in macrophages by inducing an antiviral state mediated by more different factors [4]. Studies have revealed that numbers of genes or expression levels induced by type I IFN, IL-6, and TNF pathways in response to IFN-α and IFN-ε are not identical, in spite of some overlap among IL-1α, IL-1RA, IL-4, VEFG, and GCSF [4]. IFN-α mediates more genes and upregulates genes more than [The phrasing of this edit should be checked for accuracy.…”
Section: Biological Activities Of Type I Ifnsmentioning
confidence: 99%
See 3 more Smart Citations